Super-three-dimensional fancy glaze and preparation process thereof
Through the process of modifying potassium feldspar and talc powder, combined with glaze coating and polishing treatment, the problems of insufficient surface texture and time-consuming and cost-effective polishing of traditional flower-seeking tiles are solved, and the wear-resistant and stain-resistant ultra-three-dimensional flower-seeking glaze is achieved The material enhances the three-dimensional and texture of the tiles.
Patent Information
- Application Number
- CN202411247422.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-06
AI Technical Summary
In the traditional preparation method of flower-permeable tiles, the surface texture pattern is insufficient and it is difficult to achieve three-dimensional sense. The polishing process consumes time and cost, and the bottoming phenomenon is prone to occur.
The ultra-three-dimensional flowering glaze process is adopted, and the formula and process flow of modified potassium feldspar and modified talc powder are combined with glaze coating and polishing treatment to form a wear-resistant and stain-resistant glaze layer to enhance the three-dimensionality and texture of the ceramic tile.
The three-dimensional sense of ceramic tile is improved, the bottoming phenomenon is avoided, the wear resistance, stain resistance and gloss of the glaze layer are improved, and the production cost and energy consumption are reduced.
Smart Images

Figure CN119176672A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic glaze preparation, and relates to a super three-dimensional infiltration glaze and a preparation process thereof. Background Art
[0002] Infiltrated ceramic tiles combine the wear resistance, corrosion resistance, high strength and colorful decorative effects of granite, and have become one of the indispensable leading products in building decoration materials. With the continuous development of technology, the consumption level and aesthetic level are constantly improving, and people's requirements for the decorative effects of infiltrated polished tiles are also constantly increasing. At present, in the traditional preparation method of infiltrated ceramic tiles, the texture pattern on its surface can only be printed by printing water-soluble infiltrated ink on the surface paste poured on the surface of the blank. The three-dimensional sense of the ceramic tile is insufficient, and after infiltration, the surface of the ceramic tile only produces a certain depth of decorative patterns. In the subsequent polishing process, the polishing amount needs to be accurately controlled to ensure that the decorative pattern on the surface of the ceramic tile after infiltration is not thrown away. In actual operation, multiple tests are required to determine the polishing amount, which is time-consuming and costly.
[0003] The purpose of the present invention is to propose a process and preparation method for a super three-dimensional infiltration glaze, which can realize the distribution of different textured blanks according to the inkjet infiltration pattern, improve the overall three-dimensional sense of the infiltration tile, and avoid the bottom see-through phenomenon of the infiltration tile, thereby overcoming the shortcomings of the prior art. Summary of the invention
[0004] The purpose of the present invention is to provide a super three-dimensional infiltration glaze and a preparation process thereof, which has the characteristics of wear resistance and stain resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A super three-dimensional infiltration glaze, wherein the raw materials of the infiltration glaze include glaze A and glaze B,
[0007] The raw materials of glaze A are as follows: by mass percentage, modified potassium feldspar 30-35%, sodium feldspar 40-45%, kaolin 3-5%, ball clay 2-4%, quartz 5-10%, fused quartz 10-15%;
[0008] Wherein, the preparation method of modified potassium feldspar is:
[0009] S11: mixing potassium feldspar, magnesium chloride and calcium nitrate in a mass ratio of (3-5):1:1, and grinding the mixture in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A;
[0010] S12: dispersing the mixture A in a boric acid solution to obtain a solid-liquid mixture B with a mass fraction of 20-30%, ultrasonically treating for 0.5 h, filtering, and drying at 110° C. for 8 h to obtain a mixture C;
[0011] S13: dispersing the mixture C in a 20% by mass hexadecyltrimethylammonium bromide CTAB solution, wherein the mass ratio of the mixture C to the CTAB is 1:(1-3), ultrasonicating for 0.5 h, filtering, and drying at 80° C. for 12 h. The dried mixture is heated from room temperature to 400° C. in a muffle furnace and calcined for 3 h. After the calcination is completed, the mixture is cooled and ground to a particle size of 300 meshes to obtain the modified potassium feldspar;
[0012] The raw materials of glaze B are as follows: by mass percentage, potassium feldspar 30-35%, sodium feldspar 30-40%, kaolin 3-5%, ball clay 2-4%, quartz 10-15%, fused quartz 10-15%, modified talc 2-5%;
[0013] Wherein, the preparation method of modified talcum powder is:
[0014] S21: putting talc into a ball mill and grinding it at a speed of 400 r / min for 1 h to obtain talc powder with a particle size of 200 mesh;
[0015] S22: dissolving a silane coupling agent in deionized water to obtain a silane coupling agent solution with a mass fraction of 30-50%, dispersing the talc powder obtained by grinding in S21 in the silane coupling agent solution, wherein the mass ratio of the talc powder to the silane coupling agent is 1:1, to obtain a solid-liquid mixture D;
[0016] S23: The solid-liquid mixture D is heated to 40°C, stirred at a speed of 150-200 r / min for 1-2 h, ultrasonicated for 0.5 h after the stirring, filtered, dried at 80°C for 12 h, and ground again after drying at a ball mill speed of 500 r / min for 2 h to obtain the modified talc powder.
[0017] Furthermore, the mass fraction of the boric acid solution in S12 is 10-15%.
[0018] Furthermore, the heating rate of the muffle furnace in S13 is 5°C / min.
[0019] Furthermore, the modified talc powder obtained by grinding in S23 has a particle size of 300 meshes.
[0020] A preparation process of a super three-dimensional infiltration glaze, the specific process of the preparation process of the super three-dimensional infiltration glaze is as follows:
[0021] S51: putting the raw materials of glaze A into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500 r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain glaze A;
[0022] S52: putting the raw materials of glaze B into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500r / min, and grinding is continued for 8 hours. The iron is removed by a magnetic iron remover to obtain glaze B;
[0023] S53: nitrogen is used to purge the surface of the green body, and glaze A is first poured on the surface of the green body by a pouring method. After the pouring is completed, it is allowed to stand and dry to obtain body I;
[0024] S54: pouring glaze B on the surface of body I by pouring glaze method, and after pouring, placing the body in a glaze line drying kiln for drying at a temperature of 200° C. to obtain body II;
[0025] S55: Printing the infiltration ink on the surface of the blank II, and directly putting it into the kiln for firing after printing, the kiln temperature is 1160°C, the firing cycle is 65 minutes, and after firing, it is cooled to room temperature to obtain a semi-finished product;
[0026] S56: polishing the semi-finished product obtained in S55 to obtain the super three-dimensional infiltration glaze.
[0027] Furthermore, the purge flow rate of nitrogen in S53 is 8 m / s.
[0028] Furthermore, the parameters of the glazing method in S53 are: glazing distance 25 cm, specific gravity of glaze A 1.83-1.86 g / ml, glazing amount 70 g / piece, and tile size 300*600 mm.
[0029] Furthermore, the parameters of the glazing method in S54 are: glazing distance 25 cm, specific gravity of glaze B 1.83-1.86 g / ml, glazing amount 80 g / piece, and tile size 300*600 mm.
[0030] Furthermore, the polishing process in S56 is carried out in sequence using the following grinding heads: 5 groups of 100-mesh hard modules, 4 groups of 600-mesh elastic modules, 4 groups of 800-mesh elastic modules, 5 groups of 1500-mesh elastic modules and 4 groups of 2000-mesh elastic modules.
[0031] Furthermore, in S56, the pressure applied by the grinding head of the hard grinding block for polishing to the tile surface is 1.5 MPa, and the pressure applied by the grinding head composed of the elastic module to the tile surface is 0.3-0.5 MPa.
[0032] In the formula of the infiltration glaze A and B, potassium feldspar and sodium feldspar mainly serve as fluxes to improve the vitrification degree of the glaze, quartz mainly serves to improve the mechanical strength of the glaze layer, fused quartz mainly serves to reduce the expansion coefficient, kaolin improves the suspension of the glaze slurry, ball clay improves the fluidity of the glaze slurry and prevents the glaze slurry from thixotropy, and talc mainly serves to reduce the formulation temperature;
[0033] Glaze A is poured directly on the body as a base glaze. Its main function is to make the bond between the body and the top glaze more firmly. This adhesion ensures the stability and durability of the glaze layer on the ceramic product and prevents the glaze layer from falling off or peeling off during use. This makes the ceramic product more durable during use and able to resist external impact and wear. The base glaze can also be used to cover up the color, defects or roughness of the body surface and exposed harmful minerals. By applying the base glaze, the surface of the ceramic product can be made flatter and smoother, thereby improving the aesthetics of the product.
[0034] As a basic glaze, the bottom glaze can also enhance the toughness and wear resistance of ceramic products. In the present invention, the potassium feldspar in the bottom glaze is modified to further improve the vitrification degree of the glaze. Vitrification is the process of melting and recrystallizing the glaze layer at high temperature to form a glassy glaze surface. This glaze surface has high strength and hardness, which can effectively improve the overall mechanical properties of ceramic products and make them more wear-resistant and impact-resistant. As the degree of vitrification of the bottom glaze increases, the density of the glaze layer will also increase, thereby reducing the water absorption rate of the ceramic products. Low water absorption means that the ceramic products can better resist water penetration during use, reducing expansion and cracking caused by water absorption. The vitrified glaze layer has better chemical stability and can resist corrosion from gases, liquids, acids, alkalis and other chemical substances.
[0035] In the present invention, potassium feldspar is mixed with magnesium chloride and calcium nitrate and ground. During the grinding process, the crystal structure of the potassium feldspar is destroyed to a certain extent, so that the potassium, aluminum, silicon and other elements inside the potassium feldspar are more active and easy to react with other components. Therefore, the introduction of magnesium chloride and calcium nitrate can form a new composite material, and the newly formed composite material has better flux and stability. The treatment in a boric acid solution and a CTAB solution causes chemical adsorption on the surface of the potassium feldspar composite material to form a new interface layer, which has better wettability and dispersibility and is conducive to uniform distribution in the glaze. CTAB, as a cationic surfactant, can also be adsorbed on the surface of the potassium feldspar through electrostatic action to form a stable coating layer, thereby preventing the agglomeration and precipitation of potassium feldspar particles. Boric acid, as a glass former, can effectively reduce the melting temperature of the glaze. During the modification process, the addition of boric acid can make the potassium feldspar composite material reach a melting state at a lower temperature, thereby promoting the formation and vitrification of the glaze layer.
[0036] Potassium feldspar itself has a high melt viscosity, and the modified potassium feldspar complex further enhances this property. The high-viscosity melt is more likely to form a dense and uniform glass phase during the cooling process, thereby improving the vitrification degree of the glaze; the potassium, aluminum, silicon and other elements in the modified potassium feldspar can react chemically with the quartz in the formula during the melting process to form a stable glass phase, which can be firmly attached to the ceramic body after cooling to form a smooth and hard glaze layer.
[0037] Glaze B is poured over glaze A as a top glaze. The smoothness and glossiness of the top glaze can significantly improve the texture of ceramic products. The dense structure and chemical stability of the top glaze give it excellent anti-fouling properties. It can effectively prevent stains, oil stains and other pollutants from penetrating into the interior of the ceramic, keeping the product clean and hygienic; the top glaze can resist the erosion of chemicals such as acids, alkalis, and salts, protecting ceramic products from damage. The top glaze can also improve the thermal stability of ceramic products, making them less likely to deform or crack under high temperature conditions. This is especially important for ceramic products that need to withstand high temperatures. The reduction in the top glaze formula temperature means that the energy required during the firing process is reduced. The firing of ceramic products in a kiln is a high-energy consumption process. Reducing the top glaze formula temperature can significantly reduce energy consumption and reduce production costs. Excessive firing temperatures may cause ceramic products to deform or crack due to uneven thermal stress during the firing process. Therefore, reducing the top glaze formula temperature can also help the top glaze form a uniform and dense glaze layer on the ceramic surface. This can not only improve the aesthetics of the product, but also enhance the wear resistance, corrosion resistance and other properties of the glaze. In the present invention, silane coupling agent is used to modify talc to further reduce the formulation temperature of the glaze during the preparation process.
[0038] Silane coupling agent is a kind of low molecular weight organic silicon compound with special structure. Its general chemical formula is usually RSiX 3 , wherein X represents a hydrolyzable group, and R represents an active functional group having affinity or reaction ability with a polymer molecule. When the silane coupling agent is mixed with talc and heated, the X group in the silane coupling agent will first undergo a hydrolysis reaction to generate silanol (Si-OH), and the generated silanols will further undergo a condensation reaction to form oligosiloxanes (Si-O-Si). These oligosiloxanes have a network structure. The Si-OH group of the oligosiloxane will react with the hydroxyl group (OH) on the surface of the talc to form a hydrogen bond, and dehydrate and solidify during further heating to finally form a strong covalent bond (Si-OM, wherein M represents a metal ion or group on the surface of the talc). The silane coupling agent (KH-570) used in the present invention was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0039] The dispersibility of talc powder modified by silane coupling agent in glaze is significantly improved. Since silane coupling agent forms an organic layer on the surface of talc powder, this organic layer has better compatibility with organic matter in glaze, thereby reducing the agglomeration phenomenon between talc powder particles and making talc powder more evenly dispersed in glaze; since the dispersibility of talc powder in glaze is improved, the contact area between talc powder particles and other components in glaze is increased, which helps to accelerate the diffusion of substances and chemical reactions during sintering. Therefore, under the same sintering conditions, the modified talc powder can more effectively promote the sintering process of glaze, thereby possibly reducing the required sintering temperature; a strong chemical bond is formed between talc powder modified by silane coupling agent and organic matter in glaze, and this bonding action helps to form a more dense and uniform structure in the glaze layer, and also makes the prepared glaze layer have better wear resistance.
[0040] In order to make the obtained super three-dimensional infiltration glaze have a better texture, the surface is polished after firing. In the present invention, the rigidity of the hard module and the flexibility of the elastic module are combined. When the hard module is used alone for polishing, due to the high hardness, it may cause certain damage to the glaze, such as scratches or microcracks. After the hard module is processed, the elastic module is used for supplementary polishing, which can effectively reduce these damages. The flexibility of the elastic module can avoid further scratches or damage to the glaze, and can fill and repair the minor defects that may be generated during the hard module processing. In the present invention, the pressure applied by the grinding head of the hard grinding block to the surface of the tile is 1.5MPa, and the pressure applied by the grinding head composed of the elastic module to the surface of the tile is 0.3-0.5MPa. If the pressure applied by the hard grinding head to the glaze is too large, the polishing amount is too large, resulting in excessive polishing of the glaze to expose the bottom blank, causing defects. If the pressure applied by the grinding head to the glaze is too small, the polishing amount is too small, resulting in poor flatness of the polished glaze and poor surface effect, showing more point crystals and less flash of surface crystals.
[0041] Beneficial effects of the present invention:
[0042] (1) The present invention improves the vitrification degree of the glaze by modifying potassium feldspar, introduces magnesium chloride and calcium nitrate by grinding to form a new composite, the newly formed composite has better fluxing property and stability, and chemical adsorption occurs on the surface of the potassium feldspar composite by treatment in a boric acid solution and a CTAB solution to form a new interface layer, so that the potassium feldspar composite has better wettability and dispersibility and is not easy to agglomerate and precipitate, and the potassium feldspar composite can reach a molten state at a lower temperature, thereby promoting the formation and vitrification of the glaze layer;
[0043] (2) The silane coupling agent forms an organic layer on the surface of talc through chemical action, which improves the dispersibility of talc in glaze and its compatibility with organic matter. At the same time, this modification also helps to optimize the structure of the glaze layer and promote the sintering process, thereby reducing the required formulation temperature and making the glaze layer have better wear resistance;
[0044] (3) In the present invention, the rigidity of the hard module and the flexibility of the elastic module are combined. After the hard module is processed, the elastic module is used for additional polishing, so that the obtained super three-dimensional infiltration glaze product has a better texture. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0046] Figure 1 The effect diagram of the super three-dimensional infiltrated glaze prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0048] Example 1
[0049] The formula of glaze A is as follows: by mass percentage, modified potassium feldspar 35%, sodium feldspar 40%, kaolin 5%, ball clay 4%, quartz 6%, fused quartz 10%;
[0050] The preparation method of modified potassium feldspar is:
[0051] S11: mixing potassium feldspar, magnesium chloride and calcium nitrate in a mass ratio of 4:1:1, and grinding the mixture in a ball mill at a rotation speed of 400 r / min for 1 h to obtain a mixture A;
[0052] S12: Dispersing the mixture A in a boric acid solution with a mass fraction of 15% to obtain a solid-liquid mixture B with a mass fraction of 25%, ultrasonically treating for 0.5 h, filtering, and drying at 110° C. for 8 h to obtain a mixture C;
[0053] S13: Dispersing the mixture C in a 20% by mass hexadecyltrimethylammonium bromide CTAB solution, wherein the mass ratio of the mixture C to the CTAB is 1:2, ultrasonicating for 0.5 h, filtering, and drying at 80° C. for 12 h. The dried mixture is heated from room temperature to 400° C. in a muffle furnace for 3 h at a heating rate of 5° C. / min. After the roasting is completed, the mixture is cooled and ground to a particle size of 300 meshes to obtain the modified potassium feldspar;
[0054] The formula of glaze B is as follows: by mass percentage, potassium feldspar 30%, sodium feldspar 35%, kaolin 3%, ball clay 2%, quartz 10%, fused quartz 15%, modified talc 5%;
[0055] The preparation method of modified talcum powder is:
[0056] S21: putting talc into a ball mill and grinding it at a speed of 400 r / min for 1 h to obtain talc powder with a particle size of 200 mesh;
[0057] S22: dissolving silane coupling agent KH-570 in deionized water to prepare a silane coupling agent solution with a mass fraction of 50%, dispersing the talc powder obtained by grinding S21 in the silane coupling agent solution, wherein the mass ratio of talc powder to silane coupling agent is 1:1, to obtain a solid-liquid mixture D;
[0058] S23: The solid-liquid mixture D is heated to 40°C, stirred at a speed of 200 r / min for 2 hours, and then ultrasonicated for 0.5 hours after the stirring is completed. After the ultrasonication is completed, it is filtered and dried at 80°C for 12 hours. After drying, it is ground again at a ball mill speed of 500 r / min for 2 hours to obtain the modified talc powder, and the particle size of the modified talc powder obtained is 300 mesh.
[0059] A preparation process of a super three-dimensional infiltration glaze, the specific process of the preparation process of the super three-dimensional infiltration glaze is as follows:
[0060] S51: putting the raw materials of glaze A into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500 r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain glaze A;
[0061] S52: putting the raw materials of glaze B into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500r / min, and grinding is continued for 8 hours. The iron is removed by a magnetic iron remover to obtain glaze B;
[0062] S53: nitrogen is used to purge the surface of the green body, and the purge flow rate of the nitrogen is 8 m / s. Glaze A is first poured on the surface of the green body by a pouring glaze method. The parameters of the pouring glaze method are: a pouring distance of 25 cm, a specific gravity of glaze A of 1.86 g / ml, a glaze amount of 70 g / piece, and a tile size of 300*600 mm. After pouring, the green body is allowed to stand and dry to obtain green body I;
[0063] S54: pouring glaze B on the surface of body I by pouring glaze method, the parameters of pouring glaze method are: glaze pouring distance 25 cm, specific gravity of glaze B 1.86 g / ml, glaze amount 80 g / piece, brick size 300*600 mm, after pouring, put into glaze line drying kiln for drying, the drying kiln temperature is 200°C, to obtain body II;
[0064] S55: Printing the infiltration ink on the surface of the blank II, and directly putting it into the kiln for firing after printing, the kiln temperature is 1160°C, the firing cycle is 65 minutes, and after firing, it is cooled to room temperature to obtain a semi-finished product;
[0065] S56: The semi-finished product obtained in S55 is polished, and the polishing is carried out in sequence using the following grinding heads, a grinding head composed of 5 groups of 100-mesh hard modules, a grinding head composed of 4 groups of 600-mesh elastic modules, a grinding head composed of 4 groups of 800-mesh elastic modules, a grinding head composed of 5 groups of 1500-mesh elastic modules and a grinding head composed of 4 groups of 2000-mesh elastic modules, the pressure applied by the grinding heads of the hard grinding blocks to the surface of the tiles is 1.5 MPa, and the pressure applied by the grinding heads composed of the elastic modules to the surface of the tiles is 0.4 MPa, to obtain the super three-dimensional infiltrated glaze.
[0066] Example 2
[0067] The formula of glaze A is as follows: by mass percentage, modified potassium feldspar 30%, sodium feldspar 45%, kaolin 3%, ball clay 2%, quartz 5%, fused quartz 15%;
[0068] The preparation method of modified potassium feldspar is:
[0069] S11: mixing potassium feldspar, magnesium chloride and calcium nitrate in a mass ratio of 3:1:1, and grinding the mixture in a ball mill at a rotation speed of 400 r / min for 1 h to obtain a mixture A;
[0070] S12: Dispersing the mixture A in a boric acid solution with a mass fraction of 10% to obtain a solid-liquid mixture B with a mass fraction of 30%, ultrasonically treating for 0.5 h, filtering, and drying at 110° C. for 8 h to obtain a mixture C;
[0071] S13: Dispersing the mixture C in a 20% by mass hexadecyltrimethylammonium bromide CTAB solution, wherein the mass ratio of the mixture C to the CTAB is 1:1, ultrasonicating for 0.5 h, filtering, and drying at 80° C. for 12 h. The dried mixture is heated from room temperature to 400° C. in a muffle furnace for 3 h at a heating rate of 5° C. / min. After the roasting is completed, cooling, grinding to a particle size of 300 mesh, and obtaining the modified potassium feldspar;
[0072] The formula of glaze B is as follows: by mass percentage, potassium feldspar 30%, sodium feldspar 40%, kaolin 3%, ball clay 2%, quartz 10%, fused quartz 13%, modified talc 2%;
[0073] The preparation method of modified talcum powder is:
[0074] S21: putting talc into a ball mill and grinding it at a speed of 400 r / min for 1 h to obtain talc powder with a particle size of 200 mesh;
[0075] S22: dissolving silane coupling agent KH-570 in deionized water to prepare a silane coupling agent solution with a mass fraction of 30%, dispersing the talc powder obtained by grinding S21 in the silane coupling agent solution, wherein the mass ratio of talc powder to silane coupling agent is 1:1, to obtain a solid-liquid mixture D;
[0076] S23: The solid-liquid mixture D is heated to 40°C, stirred at a speed of 200 r / min for 1 hour, and then ultrasonicated for 0.5 hour after the stirring is completed. After the ultrasonication is completed, it is filtered and dried at 80°C for 12 hours. After drying, it is ground again at a ball mill speed of 500 r / min for 2 hours to obtain the modified talc powder, and the particle size of the modified talc powder obtained is 300 mesh.
[0077] A preparation process of a super three-dimensional infiltration glaze, the specific process of the preparation process of the super three-dimensional infiltration glaze is as follows:
[0078] S51: putting the raw materials of glaze A into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500 r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain glaze A;
[0079] S52: putting the raw materials of glaze B into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500r / min, and grinding is continued for 8 hours. The iron is removed by a magnetic iron remover to obtain glaze B;
[0080] S53: nitrogen is used to purge the surface of the green body, and the purge flow rate of the nitrogen is 8 m / s. Glaze A is first poured on the surface of the green body by a pouring glaze method. The parameters of the pouring glaze method are: a pouring distance of 25 cm, a specific gravity of glaze A of 1.83 g / ml, a glaze amount of 70 g / piece, and a tile size of 300*600 mm. After pouring, the green body is allowed to stand and dry to obtain green body I;
[0081] S54: pouring glaze B on the surface of body I by pouring glaze method, the parameters of pouring glaze method are: glaze pouring distance 25 cm, specific gravity of glaze B 1.83 g / ml, glaze amount 80 g / piece, brick size 300*600 mm, after pouring, put into glaze line drying kiln for drying, the drying kiln temperature is 200°C, to obtain body II;
[0082] S55: Printing the infiltration ink on the surface of the blank II, and directly putting it into the kiln for firing after printing, the kiln temperature is 1160°C, the firing cycle is 65 minutes, and after firing, it is cooled to room temperature to obtain a semi-finished product;
[0083] S56: The semi-finished product obtained in S55 is polished, and the polishing is carried out using the following grinding heads in sequence: a grinding head composed of 5 groups of 100-mesh hard modules, a grinding head composed of 4 groups of 600-mesh elastic modules, a grinding head composed of 4 groups of 800-mesh elastic modules, a grinding head composed of 5 groups of 1500-mesh elastic modules and a grinding head composed of 4 groups of 2000-mesh elastic modules. The pressure applied by the grinding heads of the hard grinding blocks to the surface of the tiles is 1.5 MPa, and the pressure applied by the grinding heads of the elastic modules to the surface of the tiles is 0.3 MPa, to obtain the super three-dimensional infiltrated glaze.
[0084] Example 3
[0085] The formula of glaze A is as follows: by mass percentage, modified potassium feldspar 30%, sodium feldspar 40%, kaolin 3%, ball clay 2%, quartz 10%, fused quartz 15%;
[0086] The preparation method of modified potassium feldspar is:
[0087] S11: mixing potassium feldspar, magnesium chloride and calcium nitrate in a mass ratio of 5:1:1, and grinding the mixture in a ball mill at a rotation speed of 400 r / min for 1 h to obtain a mixture A;
[0088] S12: Dispersing the mixture A in a boric acid solution with a mass fraction of 15% to obtain a solid-liquid mixture B with a mass fraction of 20%, ultrasonically treating for 0.5 h, filtering, and drying at 110° C. for 8 h to obtain a mixture C;
[0089] S13: Dispersing the mixture C in a 20% by mass hexadecyltrimethylammonium bromide CTAB solution, wherein the mass ratio of the mixture C to the CTAB is 1:3, ultrasonicating for 0.5 h, filtering, and drying at 80° C. for 12 h. The dried mixture is heated from room temperature to 400° C. in a muffle furnace for 3 h at a heating rate of 5° C. / min. After the roasting is completed, the mixture is cooled and ground to a particle size of 300 meshes to obtain the modified potassium feldspar;
[0090] The formula of glaze B is as follows: by mass percentage, potassium feldspar 30%, sodium feldspar 30%, kaolin 5%, ball clay 4%, quartz 15%, fused quartz 13%, modified talc 3%;
[0091] The preparation method of modified talcum powder is:
[0092] S21: putting talc into a ball mill and grinding it at a speed of 400 r / min for 1 h to obtain talc powder with a particle size of 200 mesh;
[0093] S22: dissolving silane coupling agent KH-570 in deionized water to prepare a silane coupling agent solution with a mass fraction of 50%, dispersing the talc powder obtained by grinding S21 in the silane coupling agent solution, wherein the mass ratio of talc powder to silane coupling agent is 1:1, to obtain a solid-liquid mixture D;
[0094] S23: The solid-liquid mixture D is heated to 40°C, stirred at a speed of 200 r / min for 2 hours, and then ultrasonicated for 0.5 hours after the stirring is completed. After the ultrasonication is completed, it is filtered and dried at 80°C for 12 hours. After drying, it is ground again at a ball mill speed of 500 r / min for 2 hours to obtain the modified talc powder, and the particle size of the modified talc powder obtained is 300 mesh.
[0095] A preparation process of a super three-dimensional infiltration glaze, the specific process of the preparation process of the super three-dimensional infiltration glaze is as follows:
[0096] S51: putting the raw materials of glaze A into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500 r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain glaze A;
[0097] S52: putting the raw materials of glaze B into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500r / min, and grinding is continued for 8 hours. The iron is removed by a magnetic iron remover to obtain glaze B;
[0098] S53: nitrogen is used to purge the surface of the green body, and the purge flow rate of the nitrogen is 8 m / s. Glaze A is first poured on the surface of the green body by a pouring glaze method. The parameters of the pouring glaze method are: a pouring distance of 25 cm, a specific gravity of glaze A of 1.86 g / ml, a glaze amount of 70 g / piece, and a tile size of 300*600 mm. After pouring, the green body is allowed to stand and dry to obtain green body I;
[0099] S54: pouring glaze B on the surface of body I by pouring glaze method, the parameters of pouring glaze method are: glaze pouring distance 25 cm, specific gravity of glaze B 1.86 g / ml, glaze amount 80 g / piece, brick size 300*600 mm, after pouring, put into glaze line drying kiln for drying, the drying kiln temperature is 200°C, to obtain body II;
[0100] S55: Printing the infiltration ink on the surface of the blank II, and directly putting it into the kiln for firing after printing, the kiln temperature is 1160°C, the firing cycle is 65 minutes, and after firing, it is cooled to room temperature to obtain a semi-finished product;
[0101] S56: The semi-finished product obtained in S55 is polished, and the polishing is carried out using the following grinding heads in sequence: a grinding head composed of 5 groups of 100-mesh hard modules, a grinding head composed of 4 groups of 600-mesh elastic modules, a grinding head composed of 4 groups of 800-mesh elastic modules, a grinding head composed of 5 groups of 1500-mesh elastic modules and a grinding head composed of 4 groups of 2000-mesh elastic modules. The pressure applied by the grinding heads of the hard grinding blocks to the surface of the tiles is 1.5 MPa, and the pressure applied by the grinding heads of the elastic modules to the surface of the tiles is 0.5 MPa, to obtain the super three-dimensional infiltrated glaze.
[0102] Comparative Example 1
[0103] In this comparative example, the potassium feldspar in the glaze A is not modified, and the remaining steps are consistent with those in Example 1.
[0104] Comparative Example 2
[0105] In this comparative example, during the modification process of potassium feldspar in glaze A, magnesium chloride and calcium nitrate were not added, and the remaining steps were consistent with those in Example 1.
[0106] Comparative Example 3
[0107] In the process of modifying the potassium feldspar in the glaze A of this comparative example, no boric acid solution is used for surface modification, and the remaining steps are consistent with those of Example 1.
[0108] Comparative Example 4
[0109] In the process of modifying the potassium feldspar in the glaze A of this comparative example, CTAB was not used for surface modification, and the remaining steps were consistent with those of Example 1.
[0110] Comparative Example 5
[0111] In this comparative example, the talc in glaze B is not modified, and the remaining steps are consistent with those in Example 1.
[0112] Comparative Example 6
[0113] In this comparative example, the potassium feldspar in glaze A is not modified, and the talc in glaze B is not modified. The remaining steps are consistent with those in Example 1.
[0114] Comparative Example 7
[0115] In this comparative example, only the grinding head of the hard grinding block is used for grinding during the polishing process, and the remaining steps are consistent with those of Example 1.
[0116] The surface of the super three-dimensional infiltration glaze prepared in the embodiment and the comparative example was tested for wear resistance according to GB / T3810.7-2016, the surface stain resistance was tested according to GB / T 3810.14-2016, and the glossiness of the ceramic glaze surface was tested by a gloss meter according to GB / T 11420-2024. The experimental results are summarized in the following table.
[0117] Wear resistance (level) Stain resistance (level) Glossiness(%) Example 1 5 5 95 Example 2 5 5 90 Example 3 5 5 90 Comparative Example 1 3 4 85 Comparative Example 2 4 4 80 Comparative Example 3 4 4 80 Comparative Example 4 4 4 80 Comparative Example 5 4 3 70 Comparative Example 6 3 3 70 Comparative Example 7 3 3 50
[0118] Experimental data show that the addition of modified potassium feldspar and modified talc makes the glaze layer have better wear resistance, stain resistance and glossiness, and polishing treatment further improves the texture of the glaze layer.
[0119] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A super three-dimensional infiltration glaze, characterized in that: The raw materials of the infiltration glaze include glaze A and glaze B. The raw materials of glaze A are as follows: by mass percentage, modified potassium feldspar 30-35%, sodium feldspar 40-45%, kaolin 3-5%, ball clay 2-4%, quartz 5-10%, fused quartz 10-15%; Wherein, the preparation method of modified potassium feldspar is: S11: mixing potassium feldspar, magnesium chloride and calcium nitrate in a mass ratio of (3-5):1:1, and grinding the mixture in a ball mill at a speed of 400 r / min for 1 h to obtain a mixture A; S12: dispersing the mixture A in a boric acid solution to obtain a solid-liquid mixture B with a mass fraction of 20 to 30%, ultrasonically treating for 0.5 h, filtering, and drying at 110° C. for 8 h to obtain a mixture C; S13: dispersing the mixture C in a 20% by mass hexadecyltrimethylammonium bromide CTAB solution, wherein the mass ratio of the mixture C to the CTAB is 1:(1-3), ultrasonicating for 0.5 h, filtering, and drying at 80° C. for 12 h. The dried mixture is heated from room temperature to 400° C. in a muffle furnace and calcined for 3 h. After the calcination is completed, the mixture is cooled and ground to a particle size of 300 meshes to obtain the modified potassium feldspar; The raw materials of glaze B are as follows: by mass percentage, potassium feldspar 30-35%, sodium feldspar 30-40%, kaolin 3-5%, ball clay 2-4%, quartz 10-15%, fused quartz 10-15%, modified talc 2-5%; Wherein, the preparation method of modified talcum powder is: S21: putting talc into a ball mill and grinding it at a speed of 400 r / min for 1 h to obtain talc powder with a particle size of 200 mesh; S22: dissolving a silane coupling agent in deionized water to obtain a silane coupling agent solution with a mass fraction of 30-50%, dispersing the talc powder obtained by grinding in S21 in the silane coupling agent solution, wherein the mass ratio of the talc powder to the silane coupling agent is 1:1, to obtain a solid-liquid mixture D; S23: The solid-liquid mixture D is heated to 40°C, stirred at a speed of 150-200 r / min for 1-2 h, ultrasonicated for 0.5 h after the stirring, filtered, dried at 80°C for 12 h, and ground again after drying at a ball mill speed of 500 r / min for 2 h to obtain the modified talc powder.
2. The super three-dimensional glaze according to claim 1, characterized in that: The mass fraction of the boric acid solution in the S12 is 10-15%.
3. The super three-dimensional glaze according to claim 1, characterized in that: The heating rate of the muffle furnace in S13 is 5°C / min.
4. The super three-dimensional glaze according to claim 1, characterized in that: The modified talc powder obtained by grinding in S23 has a particle size of 300 meshes.
5. A process for preparing the super three-dimensional glaze according to any one of claims 1 to 4, characterized in that: The specific process of the preparation process of the super three-dimensional infiltration glaze is as follows: S51: putting the raw materials of glaze A into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500 r / min, and grinding is continued for 8 hours. The magnetic iron remover is used to remove iron to obtain glaze A; S52: putting the raw materials of glaze B into a ball mill according to the formula ratio, the speed of the ball mill is 300 r / min, after grinding for 1 hour, 40wt% of water, 0.1wt% of sodium carboxymethyl cellulose and 0.4wt% of sodium tripolyphosphate are added, the speed of the ball mill is increased to 500r / min, and grinding is continued for 8 hours. The iron is removed by a magnetic iron remover to obtain glaze B; S53: nitrogen is used to purge the surface of the green body, and glaze A is first poured on the surface of the green body by a pouring method. After pouring, the green body is allowed to stand and dry to obtain body I; S54: pouring glaze B on the surface of body I by pouring glaze method, and after pouring, placing the body in a glaze line drying kiln for drying at a temperature of 200° C. to obtain body II; S55: Printing the infiltration ink on the surface of the blank II, and directly putting it into the kiln for firing after printing, the kiln temperature is 1160°C, the firing cycle is 65 minutes, and after firing, it is cooled to room temperature to obtain a semi-finished product; S56: polishing the semi-finished product obtained in S55 to obtain the super three-dimensional infiltration glaze.
6. The process for preparing a super three-dimensional infiltrated glaze according to claim 5, characterized in that: The purge flow rate of nitrogen in S53 is 8 m / s.
7. The process for preparing a super three-dimensional glaze according to claim 5, characterized in that: The parameters of the glazing method in S53 are: glazing distance 25 cm, specific gravity of glaze A 1.83-1.86 g / ml, glazing amount 70 g / piece, and tile size 300*600 mm.
8. The process for preparing a super three-dimensional glaze according to claim 5, characterized in that: The parameters of the glazing method in S54 are: glazing distance 25 cm, specific gravity of glaze B 1.83-1.86 g / ml, glazing amount 80 g / piece, and tile size 300*600 mm.
9. The process for preparing a super three-dimensional glaze according to claim 5, characterized in that: The polishing process in S56 is carried out using the following grinding heads in sequence: a grinding head composed of 5 groups of 100-mesh hard modules, a grinding head composed of 4 groups of 600-mesh elastic modules, a grinding head composed of 4 groups of 800-mesh elastic modules, a grinding head composed of 5 groups of 1500-mesh elastic modules, and a grinding head composed of 4 groups of 2000-mesh elastic modules.
10. The process for preparing a super three-dimensional glaze according to claim 9, characterized in that: The pressure applied by the grinding head of the hard grinding block for polishing in S56 to the surface of the tile is 1.5 MPa, and the pressure applied by the grinding head composed of the elastic module to the surface of the tile is 0.3-0.5 MPa.
Citation Information
Patent Citations
3D infiltrated crystallization glaze and application thereof
CN109502975A
Anti-skid daily ceramics and preparation method thereof
CN109776070A
Bottom slurry for light-transmitting ceramic tile and preparation method of bottom slurry
CN110818451A
Antibacterial white porcelain glaze and processing method of antibacterial white porcelain product
CN118184142A
High-strength ceramic tile as well as preparation method and application thereof
CN118495917A
